2008
DOI: 10.1021/la802464u
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of Wettability Alteration Using Surfactants with Applications in Naturally Fractured Reservoirs

Abstract: In naturally fractured reservoirs, oil recovery from waterflooding relies on the spontaneous imbibition of water to expel oil from the matrix into the fracture system. The spontaneous imbibition process is most efficient in strongly water-wet rock where the capillary driving force is strong. In oil- or mixed-wet fractured carbonate reservoirs, however, the capillary driving force for the spontaneous imbibition process is weak, and therefore the waterflooding oil recoveries are low. The recovery efficiency can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
164
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(166 citation statements)
references
References 31 publications
2
164
0
Order By: Relevance
“…In a study, Zhu et al 2009, reported the use of a mixture of Triton X 100 (nonionic) and cetyl trimethyl ammonium bromide (CTAB) (cationic) microemulsion in lowering IFT between crude oil and the aqueous phase (brine) for additional oil recovery. Recent investigations show that cationic surfactants, for example CTAB, perform better than anionic surfactants in wettability alteration of carbonate rocks to more water wet (Saleh et al 2008).…”
Section: Alkali-surfactant Floodingmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study, Zhu et al 2009, reported the use of a mixture of Triton X 100 (nonionic) and cetyl trimethyl ammonium bromide (CTAB) (cationic) microemulsion in lowering IFT between crude oil and the aqueous phase (brine) for additional oil recovery. Recent investigations show that cationic surfactants, for example CTAB, perform better than anionic surfactants in wettability alteration of carbonate rocks to more water wet (Saleh et al 2008).…”
Section: Alkali-surfactant Floodingmentioning
confidence: 99%
“…The dead oil viscosity (0.6-33.7 cP), saturated oil viscosity (0.05-20.89 cP) and undersaturated oil viscosity (0.2-5.7 cP) having API gravity of 19.9-48, temperatures of 38-150°C, bubble point pressure of 690-25,500 kPa and pressure above bubble point (8875-69,000 kPa) were obtained from the Middle East crude oils. For such challenging reservoirs, an approach using tetraalkylammonium salt (TAS) type cationic surfactant was proposed for enhancing ORF from heavy oil-impregnated calcite cores (Saleh et al 2008). It is commonly observed that spontaneous water imbibition is not possible in oil-wet rock surfaces due to the presence of very small or negative capillary pressure.…”
Section: Surfactants Targeted Toward High-temperature High-salinity (mentioning
confidence: 99%
“…The hydrophilic head groups of adsorbed surfactant may form a small layer covering the primarily oil-wet rock surfaces, which could alter the wettability of rocks from oil-wet to water-wet state. In order to verify the ion-pair mechanism of wettability alteration, Salehi et al (2008) conducted the imbibition experiments with cationic and anionic surfactants by use of sandstones. Buckley et al (1998) reported that the pore surface of carbonate rock is usually positively charged and adsorbs acidic components in the crude oil.…”
Section: Wettability Alteration For Enhanced Oil Recoverymentioning
confidence: 99%
“…The increase in nanoparticle concentration (0-5 wt.%) increased the mobility reduction factor from 4000 to 8700 and increased foam stability. It has also been experimentally proven that the presence of nanoparticle creates better foam stability than surfactant or VES fluids and even polymer, and improves mobility control; and efficient for enhancing oil recovery owing to high sweep efficiency and effective viscosity [137][138][139][140][141][142] (Table 2). • Particle size influences porous media retention and transport behavior; SiO 2 with small particle size promote efficient penetration through the porous media…”
Section: Co 2 Storage and Leakage Inhibitionmentioning
confidence: 99%